2022
DOI: 10.1038/s41467-022-29886-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and phylogenetic uncoupling of structure and function in human transmodal cortex

Abstract: Brain structure scaffolds intrinsic function, supporting cognition and ultimately behavioral flexibility. However, it remains unclear how a static, genetically controlled architecture supports flexible cognition and behavior. Here, we synthesize genetic, phylogenetic and cognitive analyses to understand how the macroscale organization of structure-function coupling across the cortex can inform its role in cognition. In humans, structure-function coupling was highest in regions of unimodal cortex and lowest in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
104
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(110 citation statements)
references
References 131 publications
(213 reference statements)
6
104
0
Order By: Relevance
“…This is in particular notable with respect to the heteromodal vs paralimbic anchor that these two gradients radiate towards. Mounting evidence suggests that heteromodal systems, such as the default mode network, decouple from microstructurally defined axes of brain organization that mainly describe differences in laminar differentiation 38 , 116 . That work has also shown that regions with strong microstructure-function decoupling also host more flexible cognitive functions, and have marked cross-species differences between humans and nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…This is in particular notable with respect to the heteromodal vs paralimbic anchor that these two gradients radiate towards. Mounting evidence suggests that heteromodal systems, such as the default mode network, decouple from microstructurally defined axes of brain organization that mainly describe differences in laminar differentiation 38 , 116 . That work has also shown that regions with strong microstructure-function decoupling also host more flexible cognitive functions, and have marked cross-species differences between humans and nonhuman primates.…”
Section: Discussionmentioning
confidence: 99%
“…To phylogenetically map the asymmetry of functional gradients across macaques and humans, we transformed the human gradients to macaque cortex surface based on a functional joint alignment technique ( Xu et al, 2020 ). This method leverages advances in representing functional organization in high-dimensional common space and provides a transformation between human and macaque cortices, also previously used in Valk et al, 2020 ; Valk et al, 2022 .…”
Section: Methodsmentioning
confidence: 99%
“…Gradients provide a synoptic framework to capture smooth variations of connectivity patterns across the cortical mantle. They describe variations in genetic patterning ( Vainik et al, 2020 ; Valk et al, 2020 ; Valk et al, 2022 , functional processes Margulies et al, 2016 ; Murphy et al, 2018 ; Turnbull et al, 2020 ), and are observed across species ( Valk et al, 2020 ; Coletta et al, 2020 ; Xu et al, 2020 ). Gradients have been linked to graph-theoretical markers such as degree centrality ( Hong et al, 2019 ) and microcircuit dynamics ( Park et al, 2021 ) as well as connectivity distance ( Hong et al, 2019 ; Wang et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The multimodal association areas and their structural and functional connections in the human brain, primarily constituting cognitive functional networks, such as the frontoparietal network, salience network, and default-mode network, play an essential role in higher-order brain functions 10 12 . Most recent studies suggest that the development of higher-order cognitive networks in recent human brain evolution is associated with specific gene expression profiles 13 15 . The highly consistent transcriptional architecture in neocortex is correlated with resting-state functional connectivity 13 , and genetic and evolutionary uncoupling of structure and function in different transmodal systems may support the emergence of complex forms of cognition 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Most recent studies suggest that the development of higher-order cognitive networks in recent human brain evolution is associated with specific gene expression profiles 13 15 . The highly consistent transcriptional architecture in neocortex is correlated with resting-state functional connectivity 13 , and genetic and evolutionary uncoupling of structure and function in different transmodal systems may support the emergence of complex forms of cognition 15 . However, the pattern of gene expression in the human brain to support the emergence of higher-order brain functions remains to be determined.…”
Section: Introductionmentioning
confidence: 99%